A driving force analysis method for drought-flood abrupt alternation events - Li Wang; Zhe Yuan; Xiaoliang Shi; Jun Yin; Tianling Qin; Jie Zhang (Ecological Informatics)
Drought-Flood Abrupt Alternation (DFAA) events are complex hydrometeorological disasters that have become increasingly frequent under global warming, posing significant threats to socio-economic systems and the ecological stability. This study applies the Standardized Weighted Average Precipitation (SWAP) index to identify DFAA events at a daily scale in the middle and lower reaches of the Yangtze River Basin (MLRYRB) from 2001 to 2022. Additionally, a method is proposed to analyze the driving factors of DFAA and quantify the spatial distribution of dominant contributors. The results indicate that: (1) in the MLRYRB, DFAA events lasted up to 50 days and occurred 7 to 10 times in total, with the highest frequency in southern Shaanxi, central Hubei, central Anhui, and southern Jiangxi; (2) the areas affected by DTF and FTD events decreased at rates of 0.43/a and 0.62/a, respectively. DTF events were predominantly moderate in intensity, while FTD events were mostly slight; (3) the key factors driving drought-flood alternation included convective precipitation (CP), total cloud cover (TCC), top net solar radiation (TNSR), 2-m temperature (TEM), and relative humidity (RH). Regions dominated by RH and TEM accounted for 44.62 % and 30.22 % of the study area, respectively, mainly in Hubei, Hunan, Jiangxi, and Anhui. These findings offer a scientific basis for developing disaster prevention and mitigation strategies in the region.